Immuno expression pattern of proliferating cell nuclear antigen (PCNA) in normal and atretic follicles of buffalo ovary - SINGH, ADHIRAAJ; PATHAK, DEVENDRA; SINGH, OPINDER; BANSAL, NEELAM (The Indian Journal of Animal Sciences, 2019)
The present study was aimed to determine the expression pattern of PCNA in normal and atretic follicles of buffalo ovary. PCNA was localized specifically in the nucleus of the different types of cells in the ovary of buffalo. It was localized in the follicular cells of primordial and primary follicles, granulosa cells in secondary follicles and in all the compartments of a healthy tertiary follicle. The atretic follicles revealed weak PCNA expression. PCNA expression varied in different degrees of atresia and during different seasons.